Analisis kinerja keuangan Bank Muamalat Indonesia periode 2020–2024 menggunakan pendekatan Return on Assets (ROA) - salsabila, eliza; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
This study analyzes the financial performance of PT Bank Muamalat Indonesia Tbk. for the 2020–2024 period using the Return on Assets (ROA) ratio as the main profitability indicator. A descriptive quantitative method was employed, utilizing secondary data from the bank’s official annual reports and published financial statements, processed through a financial ratio approach. The results reveal that Bank Muamalat’s ROA experienced significant pressure in 2020–2021 (even recording a negative -0.05% in 2020) due to the COVID-19 pandemic, which triggered an increase in NPF and a decline in financing income. However, starting in 2022, a consistent recovery trend emerged, with ROA steadily rising to 0.30% by 2024. This improvement was primarily driven by enhanced operational efficiency (lower BOPO ratio), better financing quality control, optimization of productive assets, as well as support from national economic recovery and growing Islamic financial literacy among the public. These findings reinforce that ROA remains a relevant and effective measurement tool for assessing an Islamic bank’s ability to generate profit from its managed assets while upholding sharia governance principles. This research is expected to serve as an additional empirical reference for studies on Islamic banking performance in Indonesia.